2012
DOI: 10.1097/igc.0b013e3182412ebd
|View full text |Cite
|
Sign up to set email alerts
|

Does the FIGO 2009 Endometrial Cancer Staging System More Accurately Correlate With Clinical Outcome in Different Histologies?

Abstract: These findings describe differences in the DSS of various aggressive histologies of EC, with poorer DSS in PS, CC, or CS histologies. Analysis demonstrated the usefulness of the new FIGO staging for DSS prediction between stages IIIC1 and IIIC2 for CC and G3A, and 2 divisions for stage I rather than three.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This renewal in the staging system is supported by other studies [8,9,11,14]. Abu-Rustum et al [13] found a survival difference for 1988 stage IA and IB endometrioid carcinomas, but instead of disease specific survival they had overall survival as their end-point.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This renewal in the staging system is supported by other studies [8,9,11,14]. Abu-Rustum et al [13] found a survival difference for 1988 stage IA and IB endometrioid carcinomas, but instead of disease specific survival they had overall survival as their end-point.…”
Section: Discussionmentioning
confidence: 74%
“…A European multicenter study recruited patients with endometrioid and nonendometrioid carcinomas to analyze the disease specific survival using FIGO 1988 and 2009 systems [10]. The cause specific survival of patients with nonendometrioid carcinomas was assessed in a register-based study from the United States [11], and a study from Korea compared the overall survival of nonendometrioid carcinomas with that of grade 3 endometrioid carcinomas [12]. Lastly, overall survivals according to the two staging systems were compared in two single institution studies [13,14], one of which sought to describe survival differences for various substages of stage I endometrioid carcinomas [13].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of stage II endometrial cancer was changed in the most recent FIGO 2009 staging system; tumours with endocervical glandular involvement (previously stage IIA) were moved to stage I as this has no prognostic impact 142,143. As a result, stage II now only includes tumours with cervical stromal invasion 144…”
Section: Adjuvant Treatmentmentioning
confidence: 99%
“…142,143 As a result, stage II now only includes tumours with cervical stromal invasion. 144 Stage II tumours have been associated with an increased frequency of deep myometrial invasion and grade 3 histology, making it difficult to conclude if cervical invasion alone is the reason for the observed higher risk of recurrence and lower OS compared with stage I disease.…”
Section: High-risk Stage II Endometrial Cancermentioning
confidence: 99%
“…This zonation is not observed in any case of atypical polypoid adenomyomas or endometrial polyps. 24 Myometrial or vascular invasion is not a prerequisite for diagnosis.…”
Section: Low-grade Müllerian Adenosarcomamentioning
confidence: 99%